(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Horongkuli Village, Toari District, Kolaka Regency is known as a village that has many coconut trees and is also a producer of Virgin Coconut Oil (VCO) in Southeast Sulawesi. However, in recent years, the production of coconuts into VCO has been hampered because it is not balanced with effective production and good marketing, so that people have switched to other jobs even though the natural resources of coconuts in the village are very abundant. This study aims to increase public understanding of the potential for coconut production while fostering small-scale industries regarding VCO production. This research is a community service research using a descriptive qualitative research method, namely by providing counseling and coaching to the people of Horongkuli village. The results of the study show that through intensive training and ongoing support, residents have improved their VCO and cooking oil production capabilities, as well as their marketing strategies. This initiative has raised awareness of the importance of home industries, encouraging local entrepreneurs to utilize the abundant coconut resources available to them. Ultimately, this program has the potential to strengthen the local economy, improve farmers’ livelihoods, and contribute to sustainable agricultural practices, creating a more resilient and prosperous environment for coconut farmers in the area.